Net and Configurational Effects of Determinants on Managers’ Construction and Demolition Waste Sorting Intention in China Using Partial Least Squares Structural Equation Modeling and the Fuzzy-Set Qualitative Comparative Analysis - Yan, Guanfeng; Tian, Yuhang; Zhang, Tianhai (Sustainability, 2025)
Construction and demolition waste (C&D waste) contains various types of substances, which require different processing methods to maximize benefits and minimize harm to realize the goal of the circular economy. Therefore, it is urgent to promote the on-site sorting of C&D waste and explore the determinants of managers’ waste sorting intention. Based on a comprehensive literature review of C&D waste management, seven determinants are identified to explore how antecedent factors influence waste sorting intention by symmetric and asymmetric techniques. Firstly, the partial least squares structural equation modeling (PLS-SEM) was adopted to analyze the data collected from 489 managers to assess the net impact of each determinant on their intentions. Then, the fuzzy-set qualitative comparative analysis (fsQCA) provided another perspective by determining the configurations of the causal conditions that lead to higher or lower levels of intention. The PLS-SEM results reveal that all determinants show a significant positive relationship with the intention except for the perceived risks, which are negatively correlated with managers’ attitudes and intentions regarding C&D waste sorting. Moreover, top management support and subjective norms from other project participants and the public exhibit a huge impact, while the influence of perceived behavioral control (PBC) and policies is moderate. Meanwhile, fsQCA provides a complementary analysis of the complex causality that PLS-SEM fails to capture. That is, fsQCA identified six and five configurations resulting in high and low levels of intention to sort the C&D waste, respectively, and highlighted the crucial role of core conditions. The results provide theoretical and practical insights regarding proper C&D waste management and enhancing sustainable development.